Ten cities that led the world from ancient metropolis to modern megacity - Strathern, Paul 1940- (Hodder & Stoughton, 2022)
"From the founding of ancient capitals to buzzing modern megacities, this history of ten cities explores how urban centres have led civilisation forward. Great cities are complex, chaotic and colossal. These are cities that dominate the world stage and define eras; where ideas flourish, revolutions are born and history is made. Through ten unique cities, from the founding of ancient capitals to buzzing modern megacities, Paul Strathern explores how urban centres lead civilisation forward, enjoying a moment of glory before passing on the baton. We journey back to discover Babylonian mathematics, Athenian theatre and intellectual debate, and Roman construction that has lasted millenia. We see Constantinople evolve into Istanbul, revolutionary sparks fly in Enlightenment Paris, and the railways, canals and ships that built Imperial London. In Moscow men build spaceships while other men starve, New York's skyscrapers rise up to a soundtrack of jazz, Mumbai becomes home to immense wealth and poverty, and Beijing's economic transformation leads the way. Each city has its own distinct personality, and Ten Cities that Led the World brings their rich and diverse histories to life, reminding us of the foundations we have built on and how our futures will be shaped"--Publisher's description